Associations Between Child Maltreatment and Adolescents’ Health-Related Quality of Life and Emotional and Social Problems in Low-Income Families, and the Moderating Role of Social Support - Lo Kin-ming, Camilla (Journal of interpersonal violence, 2021)
This study aimed to examine the associations between different types of child maltreatment and health-related quality of life (HRQoL) and emotional and social problems in adolescents, and to examine the moderating effect of social support on those associations. A cross-sectional survey was conducted between January and June 2016 in Hong Kong. The sample comprised 351 parent and adolescent dyads from low-income families. The parents reported on child maltreatment (physical abuse, psychological aggression, and neglect), and the adolescents reported on their HRQoL, emotional problems, and social problems. The adolescents’ perceived social support was included as a potential moderator. Results of the study show that child physical abuse was strongly associated with emotional and social problems (B = 0.91-1.45, p < .05). Lower overall HRQoL was associated with psychological aggression (B = −3.96, p < .05) and neglect (B = −4.14, p < .05). Physical functioning was affected by psychological aggression (B = −3.16, p < .05), and emotional functioning was affected by neglect (B = −4.82, p < .05). Social functioning was impacted by all three types of maltreatment (B = −9.16 to −5.26, p < .05). This study extends previous literature by showing the varying effects of different types of child maltreatment on children’s health in the context of low-income families. The findings of this study also support that peer social support may buffer the effects of child physical abuse on adolescents’ emotional and social problems.